2021
DOI: 10.1080/07853890.2021.1947519
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium exposure induces cardiac glucometabolic dysregulation and lipid accumulation independent of pyruvate dehydrogenase activity

Abstract: Context: Suppressed glucose metabolism, elevated fatty acid metabolism and lipid deposition within myocardial cells are the key pathological features of diabetic cardiomyopathy. Studies have associated cadmium exposure with metabolic disturbances. Objective: To examine the effects of cadmium exposure on cardiac glucose homeostasis and lipid accumulation in male Wistar rats. Methods: Male Wistar rats were treated for 21 days as (n ¼ 5): Control, cadmium chloride Cd5 (5 mg/kg, p.o.), cadmium chloride Cd30 (30 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…[ 26 ] Previous studies indicated that Cd exerts negative effects on liver, kidney, bones, and cardiovascular system, which could be resulted from Cd triggering inflammatory processes and lipid accumulation. [ 27,28 ] Some previous studies suggested that kidney and liver dysfunction may lead to changes in lipid metabolism. Other population cohort studies and toxicity studies in mice indicated that kidney and liver toxicity may lead to induce lipid metabolism disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Previous studies indicated that Cd exerts negative effects on liver, kidney, bones, and cardiovascular system, which could be resulted from Cd triggering inflammatory processes and lipid accumulation. [ 27,28 ] Some previous studies suggested that kidney and liver dysfunction may lead to changes in lipid metabolism. Other population cohort studies and toxicity studies in mice indicated that kidney and liver toxicity may lead to induce lipid metabolism disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Oluranti et al, also demonstrated an adverse effect of Cd on cardiomyocyte metabolism in a rat study. In detail, Cd leads to a reduction in fasting serum insulin levels and the reduced activity of pyruvate and hexokinase, while the activity of pyruvate dehydrogenase significantly increased after treatment [ 160 ].…”
Section: The Role Of Trace Elements In Selected Cardiovascular Diseasesmentioning
confidence: 99%
“…Cd impairs the activity of potassium and sodium ATPase, and this inhibition causes elevated calcium (Ca) levels during hypertension in the smooth muscle. The main reasons for the cardiotoxicity are oxidative stress with attenuated antioxidant defenses and mitochondrial enrichment [ 14 ]. The cardiotoxicity of As is also mediated by increased oxidative stress with low antioxidant levels and mitochondrial enrichment [ 15 ].…”
Section: Toxic Trace Elements and Cardiotoxicitymentioning
confidence: 99%
“…Cd increased the weight of the heart in a rat model [ 47 ]. Similarly, another study showed that toxic chemicals increase organ weight due to the accumulation of lipids and inflammation [ 14 ]. The FFA, TC, and TG levels are increased in the Cd-exposed heart, and in a dose-dependent manner.…”
Section: Cadmium-associated Cardiotoxicity Via Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation